The Oxford dictionary of political quotations / Antony Jay - Jay, Antony
Now available in Oxford Paperback Reference, the fourth edition of the Oxford Dictionary of Political Quotations brings together both words of wisdom and things that might have been better left unsaid. A mouth-watering collection for anyone with an interest in history and politics.